Small Medium Enterprise (SME) Transaction In Salatiga - Anisa Dewi Arismaya (STIE Binaniaga, 2022)
SME are one of the drivers of the economy in Indonesia. It is proven that when Indonesia experienced an economic crisis, SME were the drivers of economic stimulus. SME in Indonesia still have obstacles in terms of financial recording and reporting. This study was conducted to find out what characteristics distinguish financial recording and reporting in SME. The results showed that based on the characteristics of the company and the characteristics of business actors, business turnover and education level were the differentiating factors for recording transactions at SME in Tingkir Village, Salatiga City. On the other hand, the age of the company in terms of company characteristics and business experience in terms of the characteristics of business actors does not distinguish the recording of transactions. The longer the age of the company and the business experience of the SME owners do not necessarily require information about recording transactions in business management. This is because business actors are not aware of the benefits that can be obtained from the application of recording transactions in business even though the age of the company and the experience of managing the business is quite long.